Uji Difusi dan Iritasi Krim Solid Lipid Microparticle Ekstrak Etanol Daun Kersen (Muntingia calaura L.) - Amriani Sapra; Radhia Riski; Nurul Hidayah (Jurnal Farmasi dan Ilmu Pengobatan, 2019)
The extract of kersen leaves (Muntingia calabura L) contains flavanoid compounds as polar antioxidants which have difficulty to diffuse through the skin. Solid lipid microparticle is a drug delivery system to improve the availability of water-soluble compounds at site of action. The aim of this study was to determine diffusion profile and irritant effect of solid lipid microparticle cream loaded ethanol extract of kersen leaves. Diffusion of solid lipid microparticle cream loaded ethanol extract of kersen leaves was carried out using Whatman no.1 membrane and circumcision by franz diffusion methods while irritation test was performed on Albino rabbits (Orytoglagus cuniculus). The results of showed profil using Whatman membrane No. 1 are better than circumcision and the irritation test results the cream do not cause irritating effects on the skin.